DESIGN OF DIGITAL CONTROL SYSTEM FOR TRAINS BRAKE PIPE SIMULATOR USING MICROCONTROLLER - Chandra, Roberto
The train braking system needs an extra precaution since the impacts caused by a train accident can be catastrophic. Unlike common automobiles, the train is equipped with a fail-safe brake system by using an indirect method to actuate the brake. The braking action of the train is controlled by the air pressure condition in the brake pipe via a brake valve. In the conventional analog brake system, the driver has to rely on intuition to set the braking force at a certain level, making the optimum deceleration value for the train hard to be achieved. As a little step to help the driver to achieve the optimum deceleration value, this research aims to design a simple digital control system simulator that can automatically determine the braking level. The designed control system focuses on the brake pipe air pressure. Arduino, as a microcontroller, is used for designing the control system. The brake valve as a component controlling the amount of brake pipe pressure is substituted with an electrical rotary switch with six positions, in which the switch position depicts braking levels from brake release to full application. Each position of the rotary switch determines a pressure setpoint for the brake pipe. Then, the brake pipe pressure is read and adjusted until reaching the setpoint. The testing of the control system is performed on a reduced version of the simulator. The pneumatic part is represented with LEDs, and the air pressure is replaced with an electrical voltage. From the testing, the control system for the reduced version of the simulator was able to perform its function for service brake and emergency braking. The brake pipe pressure voltage can adjust automatically according to the chosen braking level from the brake switch.